Dysprosium‐Doped (Ba, Sr)TiO3 Thin Films on Nickel Foilsfor Capacitor Applications. Issue 4 (12th February 2013) - Bretos, Iñigo; Schneller, Theodor; Waser, Rainer; Hennings, Detlev F.; Park, Daesung; Weirich, Thomas; Paranthaman, P.
<x xml:space="preserve">Abstract</x> The substitution in (Ba0.70Sr0.30)TiO3 thin films by the rare‐earth element dysprosium prepared at 1000°C by chemical solution deposition on nickel foils was investigated. The relatively large thermal budget applied (via annealing temperature) is shown to enhance the solubility of the Dy3+doping ion into the crystal lattice of the perovskite films. Preference for B‐site occupancy of this amphoteric cation was further promoted by the addition of BaO excess (1 mol%), which results in slightly larger grains in the films as observed by scanning electron microscopy. Despite this Ba‐rich composition, the presence of secondary phases in the thin films was not detected by X‐ray diffraction. Transmission electron microscopy revealed no evidence for local segregation of Dy at grain boundaries, neither the formation of NiO at the interface between the film and the metal foil was observed. The substitution of Ti4+ by Dy3+ leads to the formation of strong electron acceptors in the system, which balance the number of ionized oxygen vacancies arisen from the reductive crystallization atmosphere used during processing. As a consequence, the dielectric loss (tan σ) and leakage conduction measured in the resulting thin‐film capacitors were significantly reduced with respect to nominally undoped samples. The improvement of this capacitor feature, combined with the relatively high permittivities obtained in the films (490–530), shows the effectiveness of dysprosium doping within a thin‐film fabrication method for potential application into the multilayer ceramic capacitor technology.